Metaphors of Change in the Context of Eating Disorders: Bridging Understandings with Girls’ Perceptions - Mathieson, Lindsay C.; Hoskins, Marie L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Although the use of metaphor is not a new strategy in counselling or research, the literature has not fully addressed individuals’ metaphors of change and how these relate to the counselling process. Using a narrative methodology, we examined the metaphors of change provided by girls recovering from eating disorders. These rich descriptions highlighted the similarities and differences in how the girls viewed change. Furthermore, this analysis of metaphors gave us a sense of what can be learned about girls’ views of identity and agency. It is apparent that there are important implications when using metaphors in the counselling process.